Setting the stage for new ecological indicator species: A holistic case study on the Iberian dolphin freshwater mussel Unio delphinus Spengler, 1793. (April 2020) - Lopes-Lima, Manuel; Hinzmann, Mariana; Varandas, Simone; Froufe, Elsa; Reis, Joaquim; Moreira, Cláudia; Araújo, Sandra; Miranda, Fernando; Gonçalves, Duarte V.; Beja, Pedro; Sousa, Ronaldo; Teixeira, Amílcar
Highlights: Shortage of basic biological data hinder the development of meaningful indicators. We overcome this limitation for Unio delphinus through a holistic biological study. U. delphinus grows faster and is shorter-lived than most Unio species in Europe. Main hosts are native cyprinid species, while exotic fish are not effective hosts. U. delphinus is a valuable environmental indicator of largely undisturbed habitats. Abstract: Due to their sensitivity and dramatic declines, freshwater mussels are prime targets for conservation and environmental monitoring. For this, however, information is needed on life history and ecological traits, which is lacking in many taxa, including threatened species. Species recently described or recognized as valid are of particular concern, due to the shortage of even basic knowledge. A case in point is the recently recognized and Near Threatened dolphin freshwater mussel Unio delphinus Spengler, 1793, which is endemic to the western Iberian Peninsula and has suffered marked population declines. To overcome information gaps for U. delphinus, we carried out a holistic biological study across the species range, aiming to: i) estimate the area of occupancy (AOO) and extent of occurrence (EOO) based on updated distribution data taken from the literature and recent surveys; ii) estimate growth patterns from biometrical (shell dimensions and growth annuli) measurements taken on specimens from seven populations; iii) estimate sex ratios from gonad tissue biopsies collected on specimens from eight populations; iv) estimate gametogenesis and sex ratio through histological examination of gonad and gill tissues collected monthly for a year, from a single population; and v) determine host species from infestation trials of glochidia with co-occurring fish species. We estimated an EOO of 706 km 2 and an AOO of 61 km 2, which together with data on declines assigns the species to the Endangered category using IUCN criteria. Unio delphinus was found to grow faster and to be shorter-lived (up to 11 years, maturity at around 2 years old) than other European freshwater mussels. Growth and life span are similar across the range in lotic habitats, but different from that in lentic habitats. The larvae of U. delphinus may attach to most co-occurring fish species, but only native species were effective hosts. Native cyprinids, especially those from the genus Squalius, seem to be the primary hosts. Overall, the information provided contributes to a better conservation status assessment, selection of conservation and rehabilitation areas, guidance for the establishment of propagation programs and better timing for specimens' manipulation including monitoring and possible translocations. The framework presented here highlights the importance of basic biological studies to define good ecological and physiological status.